A cross-over study comparing an online versus a paper 7-day food record: focus on total water intake data and participant’s perception of the records - Monnerie, B. (Eur J Nutr, 2015)
PURPOSE: To compare (1) fluid, food and nutrient intake obtained with a paper versus an online version of a 7-day food record and (2) user’s acceptability of both versions of the food record. METHODS: A cross-over study was carried out in 2010 in France. A total of 246 participants aged 18–60 years reported their food and fluid intake using both versions of the 7-day food record, separated by a 7- to 14-day washout period. To help participants in estimating consumed portions, both versions of the food record were supported by a photographic booklet of standard portions and containers. At the end of the study protocol, participants completed a questionnaire designed to assess the acceptability of the two questionnaires. RESULTS: The reported water intake of fluids was significantly higher with the online version compared with the paper version (respectively 1348 ± 36 and 1219 ± 34 mL/day, p < 0.0001). No difference was found between methods in terms of energy intake and the consumption of most food categories, macro- and micronutrients. Furthermore, 77 % of the participants preferred the online method to the paper version. CONCLUSIONS: Fluid intake, but not food intake, reported with the online 7-day food record was higher in comparison with the paper version. In addition, the online version was preferred by users. In population surveys, the online record is therefore a relevant alternative, and even a preferred alternative in the case of fluid intake, to the paper record.